PENERAPAN SERTIFIKASI ROUNDTABLE ON SUSTAINABLE PALM OIL DALAM KELAPA SAWIT BERKELANJUTAN:STUDI KASUS WILMAR DI INDONESIA - Dinda Gayatri, Ida Ayu Sonia; Wiranata, I Made Anom; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2021): Jurnal DIKSHI, 2021)
The unsustainable management of palm oil is seen from the massive expansion of oil palm plantations that cause various adverse impacts. One of the unsustainable management of palm oil is the management of Wilmar Company in Indonesia. One of these actions is by clearing land and clearing mangrove forests in the conservation area of Balikpapan Bay in 2013.This study uses qualitative research approach and theory of effectiveness of international regimes to analyze the unachieversed stages of sustainable management characterized by impact stages. The cause of Wilmar Company's unsuccessful success in achieving sustainable management in accordance with RSPO certification standards is due to the unfulfillment of implementation on three important components. The three components are the high level of complexity of the problem, the weak problem solving capacity and the lack of full level of collaboration in the implementation of RSPO certification on the management of Wilmar palm oil in Indonesia. Keywords: Palm oil, Wilmar Company, RSPO, Indonesia